Advanced Metal Oxide Nanostructures for Environmental Remediation: Synthesis and characterization of PbO, MgO, TiO\(_2\) and Fe\(_2\)O\(_3\) - Saloua Helali; Zoubaida Landolsi; Ibtissem Ben Assaker (Chemical and Materials Sciences: Developments and Innovations Vol. 8, 2024)
Aims: This study discusses the synthesis and characterization of metal oxide nanomaterials for environmental remediation applications, with emphasis on their photocatalytic properties. Methodology: Two kinds of metal oxides, PbO and MgO, were prepared for the degradation application of textile dye methylene blue. In parallel, a porous thin film with heterojunction of TiO2 modified by polyethylene glycol (PEG) prepared by several molecular weights from 300 to 20.000 the best porous sample was covered by Fe2O3 by electrodeposition technique. PbO and MgO oxides were synthesized by coprecipitation, while TiO2-PEG/Fe2O3 heterojunction was prepared by Sol-Gel, spin coating and electrodeposition method. Structural characterization was performed by X-ray diffraction (XRD), Raman spectroscopy, and morphological analysis by atomic force microscopy (AFM) also with transmission electron microscopy (TEM). Photocatalytic performances were evaluated via the degradation of methylene blue dye. Results: PbO and MgO oxides, as well as TiO2-PEG/Fe2O3 heterojunction, demonstrated significant efficiency in the degradation of methylene blue dye, confirming their potential for environmental remediation. The results show that these nanomaterials can be effective agents for the photodegradation of organic contaminants. Conclusion: Metal oxide nanomaterials have great potential for environmental remediation applications.